The use of comparative law by courts : XIVe Congrès international de droit comparé, Athènes, 1997 = XIVth International Congress of Comparative Law, Athens, 1997 /: XIVe Congrès international de droit comparé, Athènes, 1997 = XIVth International Congress of Comparative Law, Athens, 1997. ([1999]) - Unknown
No abstract available